The Effect of Gene Mutations on Disease Severity Scores in Pediatric Familial Mediterranean Fever Patients - Şükrü Arslan; Alaaddin Yorulmaz; Vildan Güngörer (Genel Tıp Dergisi)
Objectives: Familial Mediterranean Fever (FMF) is a self-limiting autoinflammatory disease. In order to better understand the prognosis of diseases, disease severity scores are used. The aim of this study is to determine the effect of genetic mutations on disease severity scores in children with FMF. Methods: 303 patients between the ages of 0-18, who were diagnosed with FMF according to Yalçınkaya-Özen diagnostic criteria and whose gene analysis was studied, were evaluated retrospectively. Pras et al's scoring system, Mor et al's scoring system and International severity score of FMF (ISSF) scoring system were applied to all patients. Genotypes were compared according to disease severity scores. Results: When the patients were divided into 4 groups as M694V homozygous, heterozygous, M694V/other allele combined heterozygous and other mutations, according to the score of Pras et al., the frequency of mild disease tended to be less in the M694V homozygous group. When the patients divided as homozygous M694V, heterozygous M694V, heterozygous E148Q, heterozygous M694V/M680I combined mutations, according to the score of Pras et al., mild disease was found to be less common in the homozygous M694V group. When patients were divided into homozygous and heterozygous M694V groups, the disease was more severe in the homozygous M694V group according to the three scoring systems. Conclusions: Based on the scoring system described by Pras et al., the rate of severe disease was higher in patients with homozygous M694V allele, whereas the rate of mild disease was statistically significantly higher in the heterozygous group compared with homozygous group.